Microstructure and Fracture Mechanism Investigation of Porous Silicon Nitride–Zirconia–Graphene Composite Using Multi-Scale and In-Situ Microscopy - Liao, Zhongquan (Nanomaterials (Basel), 2021)
Silicon nitride–zirconia–graphene composites with high graphene content (5 wt.% and 30 wt.%) were sintered by gas pressure sintering (GPS). The effect of the multilayer graphene (MLG) content on microstructure and fracture mechanism is investigated by multi-scale and in-situ microscopy. Multi-scale microscopy confirms that the phases disperse evenly in the microstructure without obvious agglomeration. The MLG flakes well dispersed between ceramic matrix grains slow down the phase transformation from α to β-Si(3)N(4), subsequent needle-like growth of β-Si(3)N(4) rods and the densification due to the reduction in sintering additives particularly in the case with 30 wt.% MLG. The size distribution of Si(3)N(4) phase shifts towards a larger size range with the increase in graphene content from 5 to 30 wt.%, while a higher graphene content (30 wt.%) hinders the growth of the ZrO(2) phase. The composite with 30 wt.% MLG has a porosity of 47%, the one with 5 wt.% exhibits a porosity of approximately 30%. Both Si(3)N(4)/MLG composites show potential resistance to contact or indentation damage. Crack initiation and propagation, densification of the porous microstructure, and shift of ceramic phases are observed using in-situ transmission electron microscopy. The crack propagates through the ceramic/MLG interface and through both the ceramic and the non-ceramic components in the composite with low graphene content. However, the crack prefers to bypass ceramic phases in the composite with 30 wt.% MLG.